Implementasi Pasal 10 Huruf A Undang-Undang Nomor 22 Tahun 2022 Dalam Pemberian Hak Remisi Bagi Narapidana di Lembaga Pemasyarakatan Narkotika Kelas IIB Muara Sabak - Azed, Abdul Bari; Muslih, Muhammad; Marliansyah, Fadly (Legalitas: Jurnal Hukum, 2023)
In Article 10 paragraph (1) letter a of Law Number 22 of 2022 concerning Corrections, it is explained that prisoners who have fulfilled certain requirements without exception are also entitled to remission. However, in its implementation in the field, it turns out that there are various problems that arise. The aim of this research is to understand and analyze the implementation of Article 10 Paragraph (1) Letter a of Law Number 22 of 2022 in granting remission rights to prisoners in Class IIB Muara Sabak Narcotics Prison, to analyze the factors that hinder them and efforts to overcome them, as well as ideal arrangements for granting remission rights for convicts in the future. The method used in this research is empirical juridical which uses primary data. The results of the research show that the granting of remission rights to prisoners in the Class IIB Muara Sabak Narcotics Prison is guided by Article 10 Paragraph (1) letter a of Law Number 22 of 2022 concerning Corrections, but its implementation is still not effective. The factors that influence the granting of remission rights to prisoners in the Muara Sabak Class IIB Narcotics Prison consist of internal factors include: The mechanism for assessing prisoner behavior using the SPPN instrument is less effective. There are still violations committed by prisoners which result in disciplinary punishment so that the prisoner's proposal for remission is rejected. Meanwhile, the external factors are: There are still delays in the execution of court decisions by the Prosecutor's Office which results in the registration process in prison being late. Efforts to overcome this include: The prison authorities should make a step to simplify the system for assessing the behavior of correctional inmates, Activate both security and coaching programs to shape the character and stimulate changes in behavior of inmates, and Strengthen synergy between the prison authorities and the detention authorities in carrying out executions prisoner. The ideal arrangements for granting remission rights to prisoners at the Class IIB Muara Sabak Narcotics Correctional Institution in the future include: The prison authorities coordinate with the detention authorities, so that prisoners who have been detained for more than 6 (six) months can have their behavior assessed using the SPPN instrument, and the Prison authorities propose rights. remission for detainees who have been detained for more than 6 (six) months in succession with due observance of the provisions of Article 148 of Permenkumham No. 3 of 2018.